Victory in defeat : the Wake Island defenders in captivity - Urwin, Gregory J. W., 1955- (Naval Institute Press, 2011)
Told here for the first time in vivid detail is the story of the defenders of Wake Island following their surrender to the Japanese on December 23, 1941. The highly regarded military historian Gregory Urwin spent decades researching what happened and now offers a revealing look at the U.S. Marines, sailors, soldiers, and civilian contractors in captivity. In addition to exhaustive archival research, he interviewed dozens of POWs and even some of their Japanese captors. He also had access to diaries secretly kept by the prisoners. This information has allowed Urwin to provide a nuanced look at.